(untitled) (Journal of Health, Population and Nutrition, 2012)
Food insecuritynot having sufficient quantities of good-quality foodsis inversely related to physical and mental health and directly related to poor dietary intake. The objectives of this research were to (a) measure the prevalence of food insecurity among women in northern Jordan, (b) study the socioeconomic factors associated with an increased risk of food insecurity, and (c) investigate the relationship between household food insecurity and womens reported body-weight. This cross-sectional study was conducted using an interview-based questionnaire. In total, 500 women were interviewed in the waiting rooms of the outpatient clinics of two major public hospitals in northern Jordan. Food insecurity was assessed using the short form of the U.S. food security survey module. The prevalence of food insecurity was 32.4%. Income below the poverty-line, illiteracy, unemployment, rented housing, and woman heading the household were among the socioeconomic factors that increased the probability of food insecurity. No evidence was found to support the relationship between obesity and food insecurity. Except grains, food-insecure women with hunger had lower intake of all food-groups. This study demonstrated that the problem of food insecurity is present in Jordan. Food-insecure women with hunger are at a risk of malnutrition. Interventions that target reduction of the factors associated with food insecurity are necessary. DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11276 J HEALTH POPUL NUTR 2012 Mar;30(1):49-55